Pengukuran Tingkat Kedisiplinan Dan Kompetensi Terhadap Kecelakaan Kerja Pada Awak Kapal - Hanik, Kumila; Yulianto, Andri; Budi Rizqi, Noor Aini (IWJ : Inland Waterways Journal, 2024)
High discipline and hard work of the crew determine whether a task or responsibility is carried out properly, so that work accidents on board can be prevented as early as possible and the safety of the ship, crew and cargo is guaranteed. The purpose of this study is (1) to determine how discipline affects work accidents of crew in KM. Lawit, (2) to find out how the influence of competence on work accidents of Crew in KM. Lawit, (3) to find out how the influence of discipline and competence together on work accidents of Crew in KM. Lawit. This research includes field research or field research. Research place in KM. Lawit whose ship docked at Semarang Port. The data collection method uses Questionnaires/questionnaires, Documentation Sheets, Observation Sheets or Observations. The results of the study showed: (1) Discipline has a significant influence on the work accidents of ship crews in KM. Lawit, (2) there is an influence of crew competence on Work Accidents in Crew in KM. Lawit, (3) together there is an influence of discipline and competence on the work accidents of Crew in KM. Lawit.